Management tactics for patients suffering from borderline ovarian tumors in their reproductive years: in the wake of domestic and international guidelines - Vladlena M. Pernai; Marina V. Kiseleva; Mekan R. Orazov (LLC "MEDIAFORMAT", 2024)
In recent decades, the attention of the medical community has increasingly focused on the problems associated with ovarian tumors, especially on the differentiation/difference between borderline tumors and ovarian cancer. These two conditions not only have different outcomes in terms of prognosis, but also require different approaches to diagnosis and treatment, which makes them the subject of careful study and analysis. This review examines the key aspects related to borderline ovarian tumors, their classification, clinical picture and management tactics, taking into account domestic and international recommendations.